Stakeholder perceptions of offsite construction techniques: systematic review - Senger, Eduardo Werneck (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
In the past few decades, a faster uptake has been noticed for offsite construction techniques, as supported by several relevant research streams. This study focused on the perceptions of stakeholders, which is an important research field, in terms of the manifold experiences and their critical role in decision-making. The purpose of this work was to gather quantifiable information regarding benefits and barriers of offsite construction to assist in the development or improvement of tools and strategic guidelines for the decision-making process. In total, 24 papers were selected by combining the systematic review with the snowball sampling technique to survey and quantify the perceptions of 1,625 stakeholders, and to obtain 238 barrier indexes and 99 benefit indexes. A hierarchical cluster analysis was also conducted to frame 10 clusters for benefits and another 10 for barriers. In addition, a co-citation analysis was carried out to identify 7 clusters and the associated connections between them. A database was provided with barriers and benefits, ranked by their relevance to offsite construction, as well as the bibliometrics and co-citation analysis that may help choose the best-fit source/perception for the purpose of the readers.